Personalized solutions for ENT implants: The role of 3D/4D printing - Jigar Vyas; Nensi Raytthatha; Puja Vyas; Jitendra Patel (Brazilian Journal of Pharmaceutical Sciences, 2025)
Abstract 3D printing, a newer manufacturing technology, is gaining prominence in the pharmaceutical and healthcare sectors, particularly ENT implants. It enables the production of customized biological tissue scaffolds, portable models, and surgical training aids. The emergence of 4D printing offers the potential for enhancing ENT therapy safety and efficacy. The manuscript explores the potential of 3D printing to revolutionize pharmaceutical and clinical practice, enabling the development of personalized drug formulations, patient-centric implants, and anatomical models. This review delves into the emerging concept of “smart” biomaterials used in 4D printing, which are capable of mimicking natural tissues and responding to external stimuli. This paves the way for significant advancements in ENT tissue engineering with the potential to increase treatment safety and efficacy. This highlights the importance of healthcare staff in translating 3D printing innovations into clinical practice for successful adoption. The manuscript highlights the transformative impact of 3D printing in the pharmaceutical and healthcare industries. 3D printing and bioprinting technologies are revolutionizing ENT therapy, offering novel avenues for improved patient care and fostering advancements in the healthcare field.